Preparation and Physicochemical Properties of High-purity Isomaltooligosaccharides by Sequential Simulated Moving Bed Chromatography - Shenghui RUAN; Xiqun ZHENG; Xiaolan LIU; Liangyu LI (Shipin gongye ke-ji)
In this paper, isomaltooligosaccharides 50 syrup was used as raw material and purification of isomaltooligosaccharides by sequential simulated moving bed chromatography, and the related physical and chemical properties of high-purity isomaltooligosaccharide were analyzed. The stationary phase suitable for the separation of isomaltooligosaccharides was selected by single column fixed bed experiment. The separation degree of different types of cation exchange resin on isomaltooligosaccharides, monosaccharides and disaccharides mixture was compared, ZG106 K+ resin was selected as the suitable separation medium. Then, based on the single column evaluation test of preparative chromatography and the principle of material balance and the basic principle of sequential simulated moving bed. The initial operating parameters for the sequential simulated moving bed chromatographic separation high-purity isomaltooligosaccharides process were roughly determined. Further the separation conditions were optimized and the best technical parameters were as follows: feed refraction was 60% and column temperature was 65 ℃. At the same time quantity of flow in the entrance and eluent were 455 mL/h and 682 mL/h, respectively. The velocity of flow in the entrance and eluent were 40.2 mL/min and 31.8 mL/min, respectively. Besides, the circulating flow was kept within 409.5 mL/h. Finally, the outlet refraction of isomaltooligosaccharides was 18.70%. Products gained with purity was 92.80% and the yield was 83.20%. After 7 days of storage in environments with relative humidity of 43% and 81%, the moisture absorption rates of high-purity isomaltooligosaccharides were 61.63% and 67.10% respectively. Meanwhile, after 7 days of storage in environments with relative humidity of 43% and 0, the moisture retention rates of high-purity isomaltooligosaccharides were 77.96% and 15.56% respectively. Its chemical structure could still maintain high stability at 352.5 ℃. It was capable of performing the Maillard reaction. Syrup was a typical non-Newtonian "pseudoplastic fluid". Sequential simulated moving bed technology can efficiently purify isomaltooligosaccharides, which provides corresponding technical support for the large-scale commercial production and wide application of high-purity isomaltooligosaccharides. The good physical and chemical properties of high purity isomaltooligosaccharide provide a theoretical basis for its application in food and related functional sugar fields.